Accelerated Maturation, Exhaustion, and Senescence of T cells in 22q11.2 Deletion Syndrome - Smetanova, Jitka; Milota, Tomas; Rataj, Michal; Bloomfield, Marketa; Sediva, Anna; Klocperk, Adam (Journal of clinical immunology, 2022)
PURPOSE: 22q11.2 deletion syndrome (22q11.2DS) is a primary immunodeficiency characterized chiefly by the hypoplasia of the thymus resulting in T cell lymphopenia, increased susceptibility to infections, and higher risk of autoimmune diseases. The irregular thymic niche of T cell development may contribute to autoimmune and atopic complications, whereas the compensatory mechanism of homeostatic T cell proliferation and continuous immune stimulation may result in T cell senescence and exhaustion, further aggravating the immune system dysregulation. METHODS: We used flow cytometry to investigate T cell maturation, delineation, proliferation, activation, and expression of senescence and exhaustion-associated markers (PD1, KLRG1, CD57) in 17 pediatric and adolescent patients with 22q11.2DS and age-matched healthy donors. RESULTS: 22q11.2DS patients aged 0-5 years had fewer naïve but more effector memory T cells with a tendency to approach normal values with increasing age. Young patients in particular had a higher percentage of proliferating T cells and increased expression of PD1, KLRG1, and CD57, as well as cells co-expressing several exhaustion-associated molecules (PD1, KLRG1, Tbet, Eomes, Helios). Additionally, high-risk 22q11.2DS patients with very low numbers of CD4 T cells had significantly higher percentage of Th1 and Th17 T cells, driven in part by higher proportion of mature T cell forms. CONCLUSION: The low thymic output and accelerated T cell differentiation remain the principal features of 22q11.2DS patient immunity, especially in young patients of < 5 years. Later in life, homeostatic proliferation drives expression of T cell exhaustion and senescence-associated markers, suggesting functional aberrations in addition to numeric T cell deficiency.
Keywords: buněčná diferenciace; novorozenec; Infant, Newborn; Infant; Humans; Lymphocyte Count; kojenec; dítě; Th17 Cells; PD1; Child; thymus; lidé; 22q11.2 deletion syndrome; T cells; differentiation; předškolní dítě; CD4-Positive T-Lymphocytes; CD57; Adolescent; buňky Th17; Cell Differentiation; DiGeorge Syndrome; immunodeficiency; maturation; DiGeorgeův syndrom; CD4-pozitivní T-lymfocyty; počet lymfocytů; DiGeorge syndrome; Child, Preschool; mladiství